The Story of a Life : Memoirs of a Young Jewish Woman in the Russian Empire - Vygodskai͡a, Anna Pavlovna, 1868- (Northern Illinois University Press, 2012)
Anna Pavlovna Vygodskaia's autobiography, originally published in 1938, is a rare and fascinating historical account of Jewish childhood and young adult life in Tsarist Russia. At a time when the vast majority of Jews resided in small market towns in the Pale of Settlement, Vygodskaia liberated herself from that world and embraced the day-to-day rhythms, educational activities, and new intellectual opportunities in the imperial capital of St. Petersburg. Her story offers a unique glimpse of Jewish daily life that is rarely documented in public sources--of neighborly interactions, children's games and household rituals, love affairs and emotional outbursts, clothing customs, and leisure time.Most first-person narratives of this kind reconstruct an isolated and self-contained Jewish world, but The Story of a Life uniquely describes the unprecedented social opportunities, as well as the many political and personal challenges, that young Jewish women and men experienced in the Russia of the 1870s and 1880s. In addition to their artful translation, Eugene M. Avrutin and Robert H. Greene thoroughly explicate this historical context in their introduction.